Inventory Management and Competitive Advantage of Contemporary Manufacturing Firms in Nigeria - Olatunji Eniola Sule; Joseph E. O. Oshi (Newinera Publisher, 2022)
This study examined the impact of inventory management in contemporary manufacturing firms in Nigeria. This was done in relation to how effective and efficient inventory management can be used to achieve a competitive advantage in any sector such manufacturing firm may belong. This study being both exploratory and theoretical, there was critical review of inventory management and competitive advantage. The study concluded that in pursuing cost leadership and differentiation as corporate strategies, inventory management must be effective and efficient. There were recommendations based on the findings, that manufacturing firms should be proactive on issues relating to production, creation of a distinct functional department in charge of inventory management and the consideration of the use of scientific approach to inventory management.